Methodological recommendations for cognition trials in bipolar disorder by the International Society for Bipolar Disorders Targeting Cognition Task Force. (12th September 2017) - Miskowiak, KW; Burdick, KE; Martinez‐Aran, A; Bonnin, CM; Bowie, CR; Carvalho, AF; Gallagher, P; Lafer, B; López‐Jaramillo, C; Sumiyoshi, T; McIntyre, RS; Schaffer, A; et al.
Abstract: Objectives: To aid the development of treatment for cognitive impairment in bipolar disorder, the International Society for Bipolar Disorders (ISBD) convened a task force to create a consensus‐based guidance paper for the methodology and design of cognition trials in bipolar disorder. Methods: The task force was launched in September 2016, consisting of 18 international experts from nine countries. A series of methodological issues were identified based on literature review and expert opinion. The issues were discussed and expanded upon in an initial face‐to‐face meeting, telephone conference call and email exchanges. Based upon these exchanges, recommendations were achieved. Results: Key methodological challenges are: lack of consensus on how to screen for entry into cognitive treatment trials, define cognitive impairment, track efficacy, assess functional implications, and manage mood symptoms and concomitant medication. Task force recommendations are to: (i) enrich trials with objectively measured cognitively impaired patients; (ii) generally select a broad cognitive composite score as the primary outcome and a functional measure as a key secondary outcome; and (iii) include remitted or partly remitted patients. It is strongly encouraged that trials exclude patients with current substance or alcohol use disorders, neurological disease or unstable medical illness, and keep non‐study medications stable. Additional methodological considerations include neuroimaging assessments, targeting of treatments to illness stage and using a multimodal approach. Conclusions: This ISBD task force guidance paper provides the first consensus‐based recommendations for cognition trials in bipolar disorder. Adherence to these recommendations will likely improve the sensitivity in detecting treatment efficacy in future trials and increase comparability between studies.